2024
DOI: 10.1111/apt.17938
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of a third‐line rescue treatment for acute severe ulcerative colitis refractory to infliximab or ciclosporin (REASUC study)

María José García,
Sabino Riestra,
Aurelien Amiot
et al.

Abstract: SummaryBackgroundThe advent of new therapeutic agents and the improvement of supporting care might change the management of acute severe ulcerative colitis (ASUC) and avoid colectomy.AimsTo evaluate the colectomy‐free survival and safety of a third‐line treatment in patients with ASUC refractory to intravenous steroids and who failed either infliximab or ciclosporin.MethodsMulticentre retrospective cohort study of patients with ASUC refractory to intravenous steroids who had failed infliximab or ciclosporin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Nevertheless, our results showed that a third-line rescue treatment may avoid colectomy in ASUC, which was, precisely, its main purpose. 2 Since this strategy has been recently implemented in referral centres, particularly following the approval of new agents with rapid onset of action, its effectiveness needed to be evaluated. We acknowledged that this strategy is not exempt from risks.…”
Section: Editorsmentioning
confidence: 99%
“…Nevertheless, our results showed that a third-line rescue treatment may avoid colectomy in ASUC, which was, precisely, its main purpose. 2 Since this strategy has been recently implemented in referral centres, particularly following the approval of new agents with rapid onset of action, its effectiveness needed to be evaluated. We acknowledged that this strategy is not exempt from risks.…”
Section: Editorsmentioning
confidence: 99%
“…In the REASUC study, Garcia and colleagues explored third-line ASUC treatments and provided much-needed granularity to this therapeutic landscape. 2 The study comes with limitations. These include its retrospective nature, potential time bias, uncontrolled baseline differences, the bio-naïve baseline cohort, possible centre-and clinician-specific variations in practice, and the fact that patients who were historically considered for third-line therapy (vs. those who proceeded straight to colectomy) would probably be discretionary and chosen without defined criteria.…”
mentioning
confidence: 99%